Scedosporiosis Transmission from Near-Drowning Donor to Kidney Recipient: A Case Report and Literature Review - Yang, MD, PhD, Bei; Kohli, MD, Romesh; Tomaszewski, MD, John E; Liu, MD, PhD*, Lin (North American Journal of Medicine and Science, 2022)
Infection is a common complication following a near-drowning event. Near-drowning victims as organ donors carry an increased risk for donor-derived infection. We report a rare case of donor to recipient transmission of scedosporiosis in a kidney transplant from a near-drowning organ donor. The patient is a 62-year-old male who received his second deceased-donor kidney transplant from a young man who died of freshwater drowning. The patient’s clinical course was complicated when the heart recipient from the same donor died of invasive scedosporiosis, and the other kidney recipient from the same donor lost the graft due to kidney fungal infection. Our patient had no symptoms with negative urine and blood cultures. Kidney biopsies on three different occasions were performed and revealed no evidence of fungal infection. However, given the high mortality rate of scedosporiosis, the grafted kidney was eventually explanted on the 37th day post-transplantation. Two small cystic lesions were found in the explanted kidney, and microscopic examination with Grocott methenamine silver (GMS) stains revealed fungal colonization within these two cystic lesions. Scedosporium spp. were further identified by PCR. In conclusion, near-drowning donors pose an increased risk for donor-derived scesdoporiosis. Routine screen tests are not sensitive enough to detect scesdoporium infection pre- or post-transplantation. Scedosporiosis is intractable, with a high mortality rate and graft loss in organ recipients. [N A J Med Sci. 2022;15(1):013-016. DOI: 10.7156/najms.2022.1501013] Key Words: near-drowning donor; donor-derived infection; scedosporiosis